PENERAPAN MODEL PEMBELAJARAN KOOPERATIF BERMAIN JAWABAN UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI IPA SMA - Jumi Handayani; Erviyenni Erviyenni; Rini Rini (Pascasarjana Universitas Negeri Medan, 2014)
Abstract The Research on application of cooperative learning to play the answer has been done to improve student achievement on the subject of colloid in class XI IPA SMAN 5 Pekanbaru on May 20th until June 05th. Form of research is experimental research with pretest-posttest design. The sample consist of two class, namely class XI IPA 5 as the experimental class and class XI IPA as control class which randomly selected after had tested normality and homogeneity. Experimental class is a class that implemented cooperative learning model playing the answers while the control class used discussion information methods. Data analysis technique used is the t-test. Based on the results of the final data processing using t-test formula obtained tcount>ttable (3,042 > 1,67) means the application of cooperative learning model playing the answers can improve student achievement on the subject of colloids in class XI IPA SMAN 5 Pekanbaru, with an increasing percentage of 11,5 % .Keywords : Playing Answer, Cooperative Learning, Learning Achievement, Colloid